Hyphomycetes from north Maharashtra - Patil, S Y; Wagh, D D; Borse, B D (Current Botany, 2012)
The present paper deals with five species of Dematiaceous Hyphomycetes were collected from the submerged wood samples from the various water bodies in North Maharashtra region. Two species viz. Camposporidium cristatum Nawawi and Kuthubutheen and Dictyosporium guanttii Bhat and Sutton are being recorded for the first time form India. While Bactrodesmium indicum Udaiyan and Diplocladiella longibrachiata Nawawi & Kuthubutheen are being reported for the first time from Maharashtra state. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.